The Mediating Role of Work Engagement Between the Influence of Learning Culture on the Learning Agility of Millennial Employees - Benedikta Gaudensia Sura; Reny Yuniasanti; Nina Fitriana (Universitas Islam Negeri Raden Intan Lampung, 2025)
The study examines how learning culture affects learning agility among millennial employees at Company